SLAMF7 (CD319) enhances cytotoxic T-cell differentiation and sensitizes CD8+ T cells to immune checkpoint blockade - Sander, Jan-Erik; Han, Irina; Fickenscher, Lisette; Schmidt, Jörg-Peter; Kroll, Hartmut; Vosikova, Tereza; Durisin, Martin; Lingel, Holger; Brunner-Weinzierl, Monika C. (Frontiers in Immunology, 2025)
Tumors frequently evade immune destruction by impairing cytotoxic CD8+ T-cell responses, highlighting the need for strategies that restore T-cell functionality. Here, we identify SLAMF7 (CD319) as a key enhancer of human CD8+ T-cell responses against tumors. SLAMF7 expression is induced by pro-inflammatory signals such as IL-12 and CD28 co-stimulation. Agonistic SLAMF7 signaling, in synergy with TCR activation, is able to strongly induce T-cell activation and clonal expansion, a finding consistently observed in CD8+ T cells from healthy adults as well as derived from blood and tumor-draining lymph nodes of patients with head and neck squamous cell carcinoma (HNSCC). Moreover it drives a distinct differentiation programme characterized by elevated expression of key transcription factors Eomes and T-bet, leading to increased production of effector molecules such as Interferon γ, Granzyme B and Perforin. In contrast to CD28 costimulation, SLAMF7 activation also promotes serial killing potential via BTLA induction. In antigen-specific human models, SLAMF7 activation boosts CD8+ T-cell responses against the tumor-associated antigen NY-ESO-1, a key target in several cancers including HNSCC. Moreover, combining SLAMF7 activation with PD-1/PD-L1 immune checkpoint blockade synergistically enhances cytokine release and cytotoxic potential, highlighting its potential to overcome immunosuppression and reinvigorate antitumor immunity.